CHARACTERISTICS OF LEAVES TRICHOMES OF FAGONIA L. (ZYGOPHYLLACEAE) IN SAUDI ARABIA - D. Alshehri, Manar; A. Bukhari, Najat; S. Alwahibi, Mona (International Journal For Research In Agricultural And Food Science, 2022)
The characteristics of the leaf epidermis play a distinctive role in support of taxonomic studies within plants. However, we did not find taxonomic studies in Saudi Arabia of leaf epidermis, especially the trichomes of species in the genus Fagonia L. that are considered one of the most important medicinal genera in the Zygophyllaceae family, recorded in the Flora of Saudi Arabia. In this paper, the trichomes of Fagonia species leaves are determined. The upper and lower surfaces of leaves in all studied species had many types of trichomes with varying densities, except F. schwinfurthii leaves were smooth with sparse trichomes on their petioles. All trichomes in the studied species were unbranched glandular. Each species had more than one type of glandular trichomes. Some of the trichomes were sessile and others had stalks. The studied species contained multiple forms of secretory cells. The most common shapes were the oblong and clavate secretory cells. Also, the secretory cells had other shapes, such as cylindrical, pyriform, spherical, capitate, pilate, digitiform, and hook-shaped. The secretory cell of some species contained a cupule, but F. tristis was distinguished by the radial shape of a cupule. In this study, the multiple differences in secretory cell shapes demonstrated the distinguish diversity of trichomes and recorded new shapes that were not previously observed in Fagonia L.